The role of leaders’ strategic improvisation, corporate entrepreneurship, organizational culture, and total quality management on the performance of international SMEs in UAE - Alzarooni, Majid Ibrahim Mohamed Abdalla (2022)
The UAE's export has long been relying on the extraction and distribution of petrochemicals, and little or no attention has been given on the development of other economic sectors such as SMEs. Thereby, the prime objective of this study is to examine the impact of Total Quality Management, Leaders’ Strategic Improvisation, and Corporate Entrepreneurship on the performance of international SMEs in the UAE. In addition to that, the study also examines the mediating role of Corporate Entrepreneurship in the relationship between Total Quality Management, Leader’s Strategic Improvisation, and the performance of international SMEs in the UAE. Finally, the study also studies the moderating role of Organizational Culture in the relationship between Corporate Entrepreneurship and the performance of international SMEs in the UAE. The data was analysed using SPSS and PLS-SEM. Critical levels of 0.05 and 0.01 of significance were used to test the hypotheses. In this study, 8 hypotheses out of 9 are supported while only one is not supported. The hypotheses regarding the direct relationships between Total Quality Management and Leader’s Strategic Improvisation on SME Performance are supported. Likewise, the hypotheses regarding the mediating role of Corporate Entrepreneurship in the relationships between Total Quality Management and Leader’s Strategic Improvisation with SME Performance are also supported. Meanwhile, the hypothesis testing regarding the moderating effect of Organizational Culture on the relationship between Corporate Entrepreneurship and SME Performance reaches the conclusion that SME managers should focus on quality management practices as well as the building of strategic improvisation quality among their leaders in order to enhance the performance of their firms. Also, SME management must try to enhance the entrepreneurial culture and innovative thinking of their employees towards achieving sustainable performance and strategic competitive advantage.